Pelatihan Koreografi Tari Anak Menggunakan Musik Ansambel untuk Guru Sekolah Dasar di Gugus 2 Kota Malang - Cicilia Ika Rahayu Nita; Andika Gutama; Wiji Setyaningsih (Pelita: Jurnal Pengabdian kepada Masyarakat, 2021)
The purpose of this training is to provide children's dance choreography training using ensemble music for elementary school teachers in cluster 2, Malang city. This training uses the lecture method, demonstration method and assignment method. The participants in this training were elementary school teachers in cluster 2 of Malang city which consisted of ten elementary schools, namely SDN Bandungrejosari I to IV, SDN Bakalan Krajan I to IV, SD IGS and MI Insan Mulia. The results of this training show that the children's dance choreography training activity using ensemble music was welcomed by teachers in cluster 2 of Malang city. The teachers are of the opinion that children's dance choreography training activities using ensemble music can add information and knowledge about SBdP material, especially dance and music, to be applied in learning activities. With this activity, the teacher responded positively because it could add insight and improve teacher skills.